3-D predictions of installation and group effect on driven piles in sands. Issue 1 (February 2015) - Freitas, Alessandra Conde de; Danziger, Bernadete Ragoni; Pacheco, Marcus; Gerscovich, Denise Maria Soares
<x content-type="archive" xml:space="preserve">Abstract</x> The installation of individual piles driven in sands increases the soil density and the soil strength around the pile, providing generally a beneficial effect toward the pile capacity. The simultaneous effect of pile installation and pile group interaction is generally difficult to predict by the classical pile analysis procedures, although more recent advances in academic and commercial programs for numerical analyses have the potential for providing a better understanding of this complex interaction. In this paper, the simultaneous effects of pile installation and pile group are investigated by 3-D FE analysis, by taking into account the soil densification around an individual driven pile. The finite element program Plaxis 3D Foundation is used to model a documented case study of a small-scale piling group in sands, taking into consideration the initial state of the soil before installation and the soil improvement after driving. The revised and improved parameters of the sand after the installation are used in this paper to model a 9-pile group with different pile spacing, to account for the simultaneous effect of sand densification and pile group. The comparison of the experimental values with those simulated numerically shows reasonably good agreement.